The Challenges in the Fight against COVID-19 Pandemic: A Qualitative Study - Shamsudeen Ademola Sanni; Neema Rajabu; Ali Olugbenga Yusuf (Journal of Health Promotion and Behavior, 2021)
Background: COVID-19 pandemic has dominated the global space for more than a year, and the world faces a lot of challenges in the battle against the deadly virus. This study highlights fundamental issues that undermine the fight against the COVID-19pandemic and informs on how government and health authorities might further the cause of pandemic control. This study aimed is to analyze challenges that hinder the battle against the COVID-19pandemic from the viewpoint of the Nigerian Twitter community.Subjects and Method: This was a qualitative study with phenomenological approach, conducted using an online survey through Google Forms with Nigerian Twitter community. A total of 128 informants were selected using a list-based sampling technique. The data was managed, cleaned, organized and analyzed in SPSS, Microsoft Excel Spreadsheet, Microsoft Word and Microsoft Notepad.Results: 40.6% of the informants are in the field of Education, 11.7% are Entrepreneurs, 10.9% are Students, 10.9% are Civil Servants, 9.4% are IT Specialists, while 7.0% are Engineers. Issues that undermines the fight against COVID-19pandemic according to the findings from this study were summarized and classified into five themes, included: 1) Fake News Distort Health Messages on Covid-19, 2) Conspiracy Theories on Covid-19, 3) Mismanagement of COVID-19pandemic, 4) Lack of Government Trust on Covid-19, 5) Lack of Adequate Information on Covid-19.Conclusion: Findings suggest that these five issues are key in fighting the COVID-19scourge and must be addressed in future pandemic mitigation efforts and control plans.Keywords: COVID-19, health communication, fake news, pandemic, health messagesCorrespondence: Sanni Shamsudeen Ademola. Department of Computer Science, Faculty of Science and Engineering, University of Eswatini. Private Bag 4, Matsapha Manzini, The Kingdom of Eswatini. Email: sanniade01@gmail.com. Mobile: +26876241155/ 79241155Journal of Health Promotion and Behavior (2021), 06(02): 133-143DOI: https://doi.org/10.26911/thejhpb.2021.06.02.06